ANALISIS KELAYAKAN DAN KEBERLANJUTAN USAHA PADA NOTIONBOX CV KOTAK KREATIF INDONESIA - Dwi Nadya.S, Siti Zalsadila; Muhammad, Ashar (ADMIT: Jurnal Administrasi Terapan, 2025)
This study was conducted to evaluate the feasibility and sustainability of NotionBox, a creative agency under CV Kotak Kreatif Indonesia. The method used was a descriptive approach utilizing primary and secondary data. The business feasibility assessment covered five main aspects, namely legal, marketing and market, technical-operational, managerial and organizational, and financial aspects. Financial analysis was conducted using the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Average Rate of Return (ARR), and Profitability Index (PI) approaches, which collectively indicate that the business is economically viable. Additionally, the sustainability of the business was assessed through three key dimensions: economic, social, and environmental. The study results indicate that NotionBox is not only viable from a business perspective but also has a strong foundation for long-term sustainability. Keywords: creative agency, business viability, business sustainability, creative industry